PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 005 RAJA BEJAMU - Zairobi '; Eddy Noviana; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is the low learning outcomes IPS, with the average achieved learning outcomes at 54.40 with the percentage of 48.00% completeness. The low yield is due to the study: (1) the conventional learning methods, so that learning becomes monotonous; (2) in the learning group of students did not perform the learning activities together so that students with low ability more passive or throwing responsibility; (3) the lack of cooperation activities among students on group learning so that the students' understanding of each other is different; and (4) teacher-centered learning, so that students can not distribute inspriasi in learning. Based on this the researchers conducted a study class action by implementing cooperative learning model NHT. This research was conducted at SD Negeri 005 Raja Bejamu, with research subjects fourth grade students with enrollment of 25 students, with details of 15 male students and 10 female students. This research was conducted as many as two cycles, data collection techniques used were observation and written tests. The study states that the implementation of inquiry learning model can increase the activity of teachers and students and learning outcomes IPS. This is evidenced by: (a) the activities of teachers in the first cycle of meetings I earn a percentage of 58.30% in the first cycle II meeting to obtain a percentage increase of 62.50%. In the second cycle was a meeting I earn a percentage 79.20% and in the second meeting of the second cycle gained 91.67%; and activities of students in the first cycle teacher meeting I earn a percentage of 54.20% in the first cycle II meeting to obtain an increase of the percentage of 58.30%. In the second cycle was a meeting I earn a percentage of 75.00% and in the second meeting of the second cycle gained 87.50%. (B) mastery learning students has increased, the base score rose to 16 people in the first cycle, then increased to 21 people in the second cycle. The average learning outcomes increased from a base score is 54.40 into 65.80 in the first cycle and 73.80 in the second cycle.Keywords: cooperative learning model NHT, learning outcomes IPS